Influence of river discharge, dissolved nutrients, and Asian carp on suspended particle dynamics in Navigation Pools 19 and 20 of the Upper Mississippi River - Milde, Amanda S. (My University, 2016)
Suspended particles are an essential component of large rivers, for example in shaping channel geomorphology, biogeochemical cycling of nutrients, and are primary food web resources. The Upper Mississippi River (UMR) is a large floodplain river that exhibits pronounced spatiotemporal variation in environmental conditions and biota, providing an idea environment for investigating suspended particle dynamics of large river ecosystems by addressing two questions: (1) How do suspended particle characteristics (e.g., size and morphology) vary temporally and spatially? and (2) What environmental variables have the strongest association with particle characteristics? Water sampling was conducted in June, August, and September 2013 and 2014 in Pool 19 of the UMR. Water variables were analyzed according to standard methods. A FlowCAM particle imaging system was used to enumerate and measure particles 53–300 μm in diameter for size and shape characteristics (e.g., volume and elongation). Particle characteristics varied considerably over space and time and were strongly associated with discharge and concentrations of nitrate + nitrite (NO3-) and soluble reactive phosphorous (SRP). Particle characteristics from backwaters were distinct from those from other habitats likely due to reduced hydrologic connectivity and higher biotic production in backwaters. Relatively greater proportions of phytoplankton and zooplankton were observed during low discharge and concurrently with higher relative chlorophyll, volatile suspended solids, and total phosphorous concentrations in all habitats. Examining the dynamics of suspended particle characteristics in the UMR provides insight into the complex interactions among river flow, geomorphology, and nutrients as drivers of suspended particle dynamics in large floodplain rivers.
Keywords: Silver carp--Control--United States; Mississippi River; Bighead carp--Control--United States